Comparison of Personal Profile and Risk Factors between Patients with Ischaemic and Haemorrhagic Stroke - Ali Masum, Abu Shams Md Hasan; Ara, Kazi Jannat; Saeed, Atia; Shams, Shakil; Mohiuddin, Md; Hannan, MA; Sabuj, Md Shahidullah; Fatema, Nilufar (University Heart Journal, 2019)
Stroke is the third leading cause of death in adult population throughout the world and is the most common cause of severe adult physical disability. It is increasing at an alarming rate in Asia including Bangladesh. The assessment of the frequency of development of various types of complications of stroke is important for proper management after acute stroke and its primary and secondary prevention. The aims of the study were to observe the complications in patients with ischemic and hemorrhagic stroke.A cross sectional observational study was conducted from September 2015 to April 2017 in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. All the patients of ischemic and hemorrhagic stroke confirmed by neuroimaging (CT scan of head/ MRI of brain), meeting the inclusion and exclusion criteria were included in the study.Our study was performed with eighty stroke patients. Among them sixty five were ischemic and fifteen were hemorrhagic stroke patients. Present study showed that maximum stroke patients were more than 50 years of age. Mean age of the study population was 59.28 ± 13.98 years and 60.07 ± 17.29 years in ischaemic stroke patients and haemorrhagic stroke patients respectively. Stroke incidence rate is 1.25 times greater in men than women. University Heart Journal Vol. 15, No. 2, Jul 2019; 42-46